Identification of differentially expressed proteins in atherosclerotic aorta and effect of vitamin E - YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (ELSEVIER, 2013)
Atherosclerosis is a chronic inflammatory disorder that occurs as a result of mononuclear lymphocyte infiltration to the arterial wall, smooth muscle cell proliferation and damage in the arterial wall caused by extracellular matrix accumulation. Besides several genetic and environmental factors, increased serum cholesterol and oxidized low density lipoproteins are considered to be major inducing factors of atherosclerosis. Several protective agents have been used to prevent the progression of atherosclerosis and recently vitamin E has been focused because of its significant role in signaling mechanisms. Since many different cell types are involved in the development of hypercholesterolemia induced atherosclerosis, it is important to investigate wide range of proteins to highlight the pathologic and diagnostic mechanisms. In this study, by using proteomic technique, we identified differentially expressed proteins following cholesterol and also vitamin E treatments. The expressions of apolipoprotein AI and apolipoprotein E involved in lipid metabolism, peroxiredoxin 1, peroxiredoxin 2 and thioredoxin involved in antioxidant system, 14-3-3 protein zeta delta and 14-3-3 protein beta alpha in cell signaling, biglycan, vimentin, tropomyosin and smooth muscle a-actin as structural and contractile proteins have been discussed. Biological significance We observed several protein alterations in aorta of cholesterol fed and vitamin E treated rabbits. These differentially expressed proteins associated with key mechanisms involved in atherosclerosis and signaling mechanisms related with vitamin E. These findings for different proteins might be helpful for deciphering the pathogenesis in atherosclerosis. In addition it provides a new perspective to understand mechanisms of beneficial effect of vitamin E on the signaling pathways in atherogenesis. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Atherosclerosis; Hypercholesterolemia; Vitamin E; Proteomic; LOW-DENSITY LIPOPROTEINS; CORONARY-HEART-DISEASE; ALPHA-TOCOPHEROL; KINASE-C; APOLIPOPROTEIN-E; PROTEOMIC ANALYSIS; OXIDATIVE STRESS; ANTIOXIDANT; QUANTIFICATION; INFLAMMATION